Training needs for teachers of the first cycle in accordance with the national standards for curriculum year pre-university education from the point of view "Descriptive study in the schools of the city of Lattakia" (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The goal of current research to know for teachers of the first episode of training needs in accordance with the national standards for curriculum year pre-university education from their point of view, the aim of the research is also to know the differences in these requirements, according to the variables of experience and qualifications, and reached the sample (125) teachers were randomly selected schools of the city of Latakia, as the number of the original members of the community amounted according to the Department of Education to 2015 statistics (2480) teachers. To reach the objectives of the research were to adopt a list of training needs in accordance with the national standards for curriculum year pre-university education prepared by the researcher (Appendix 2). The results confirmed the presence of various training needs of teachers in the field of planning, implementation, and evaluation, and the results showed the existence of differences between the identification of teachers to these needs, according to a changing experience for the benefit of experienced between 5-10 years and for variable Qualification for the benefit of holders of certificate of educational qualification diploma.